Dangers of eating bushmeat - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Bushmeat, an umbrella term for all edible species of wildlife, includes not only deer, snakes, and elephants, but also chimpanzees and gorillas. Opening up African forests for logging also opens up the road to wildlife. Timber companies hire hunters...